2010
DOI: 10.1590/s0034-72802010000100009
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic orbital fracture with intact ocular globe displacement into the maxillary sinus

Abstract: The authors report one case of orbital fracture of the floor and the medial walls after trauma with an intact ocular globe displacement into the maxillary sinus. The same authors emphasize the treatment, complications and the rarity of this case. In this case the patient developed a good visual acuity and a loss of ocular motility as complication (except abduction) .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 9 publications
1
7
0
1
Order By: Relevance
“…Visual prognosis is generally poor in such cases since the retina and optic nerve are very sensitive to the injury and ischemia, although recovery of a normal vision has been reported in some cases. 3,28,30,33,36,37,[39][40][41] The obtained outcome in the present case supports the opinion of Müller-Richter et al 36 as they stated in their discussion that the very satisfying results were due to the fact that the orbital floor broke in the posterior part, reducing the strain on the muscles and optic nerve during the dislocation, and preventing their laceration.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Visual prognosis is generally poor in such cases since the retina and optic nerve are very sensitive to the injury and ischemia, although recovery of a normal vision has been reported in some cases. 3,28,30,33,36,37,[39][40][41] The obtained outcome in the present case supports the opinion of Müller-Richter et al 36 as they stated in their discussion that the very satisfying results were due to the fact that the orbital floor broke in the posterior part, reducing the strain on the muscles and optic nerve during the dislocation, and preventing their laceration.…”
Section: Discussionsupporting
confidence: 86%
“…1,3,38 Nine had postoperative vision. 3,28,30,33,36,37,[39][40][41] Our case represents the 20th reported case of dislocated globe into maxillary sinus, the 10th case with postoperative vision recovery, and the 2nd reported case with recovery of visual acuity after initial postoperative no light vision (►Table 1).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Severe injuries with sufficient force can disrupt this soft tissue protection and cause the globe to herniate or subluxate. [ 1 2 3 4 5 6 7 8 ] Review of the literature revealed 25 cases of traumatic globe dislocation into the sinuses, only eight of whom regained complete or partial vision[ 1 2 3 4 5 6 7 8 ] [ Table 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Review of the literature yielded 25 such cases with only eight patients reporting complete or partial visual recovery. [ 1 2 3 4 5 6 7 8 ] We report a case of traumatic globe dislocation with partial visual recovery. We also reviewed the literature for the mechanism of injury, timing of surgical intervention, and final visual outcome in cases of traumatic globe dislocation.…”
mentioning
confidence: 99%